WAYS TO OPTIMIZE THE STRUCTURE AND FUNCTIONS OF INFORMATION TECHNOLOGY MANAGEMENT IN PUBLIC AUTHORITIES - YERMOLENKO, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The introduction of electronic document management systems in local governments provides an opportunity to improve management decisions, speed up relations between authorities, to process information better and faster. Unfortunately, there are now many tasks and obstacles to the effective use of electronic document management in the country, which are primarily due to the lack of an effective mechanism for its implementation, compliance with the principles of connectivity, setting up electronic interaction between government and local authorities. self-government bodies, compliance of technological and technical bases with today's needs. The purpose of the article is to provide recommendations on ways to optimize the structure and functions of information technology management in public authorities.Due to the fact that information-analytical practice is an extremely important element of any function of public management, in the structural sense, the mechanism of information-analytical support of public management should be reflected in the main functions from among those that follow from the essence of management. Given the activities for their implementation, the functions of coordination and organization and the functions of control and analysis should be brought together, the function of regulation of its essence should be reproduced in the form of feedback. The main reasons that cause the shortcomings of informatization are identified. The issue of development, implementation and modernization of information systems, which requires the introduction of technical conditions for some processes can be considered solved if the information that appears in the information system is true, up-to-date and based on a system of grouped targets. Modernization of information and analytical support should be carried out in the direction of the main priorities of modernization of the state and administrative mechanism in general. To solve this task, the paper provides conceptual provisions of the mechanism of information and analytical support of public administration. Their implementation will be able to provide a set of methodologies for building information systems, more deeply use the opportunities of informatization in determining the relevance of the consequences of information and analytical work to consumer requirements (civil servants in various governments, external consumers, for example, population and business) and reduce costs by automating information processing, which in total represents the methodological basis of the mechanism for implementing the Concept of e-Government Development and the National Informatization Program in the fragment of information and analytical support of public administration.Prospects for further research are to develop favorable conditions for the development of the next stage of implementation of e-government - digitalization of government and the entire economy of Ukraine.
Keywords: information; information-analytical support; electronic document circulation; digital transformation; public authority